Nesting ecology of Florida mottled ducks using altered habitats. Issue 5 (11th March 2013) - Varner, Dana M.; Bielefeld, Ronald R.; Hepp, Gary R.
Abstract Habitat loss has negatively affected many species of upland‐nesting waterfowl. Very few areas contain pristine nesting habitat in Florida because of conversion to agriculture and urban development. Although some species have acclimated to nesting in an altered landscape, little is known about the nesting ecology of Florida mottled ducks (Anas fulvigula fulvigula) that use altered habitats. We located and monitored 77 nests of radio‐marked Florida mottled ducks in the Upper St. Johns River Basin (1999–2002) and in south Florida (2009–2011) and tested the effects of nest vegetation characteristics, human disturbance, and temporal variables on estimates of daily nest survival. We also calculated the percent of females that nested each year as a measure of breeding propensity. Nest age at discovery had a positive relationship with daily nest survival. Daily nest survival rates did not vary within or among years and were unaffected by density and height of vegetation at the nest and human disturbance parameters we measured. Breeding propensity ranged from 25% to 56%. Breeding propensities were less than those of other duck species, but our nest success estimate of 28% was greater than most estimates for ducks and is not likely to limit population growth of Florida mottled ducks. © 2013 The Wildlife Society.